An efficient framework for integrating distributed generation and capacitor units for simultaneous grid‐connected and islanded network operations. (22nd April 2021) - Leghari, Zohaib Hussain; Hassan, Mohammad Yusri; Said, Dalila Mat; Memon, Zeeshan Anjum; Hussain, Saddam
Summary: This paper proposes a two‐stage planning approach for the efficient utilization of distributed generation (DG) and capacitor banks (CBs) for the simultaneous grid‐connected and islanded operations of the balanced distribution networks. The first stage determines the optimal installation locations and capacities of DGs and CBs using an improved variant of the Jaya optimization algorithm (IJaya) to minimize the power losses and voltage deviation during the grid‐connected operation of the distribution network. The second stage identifies the optimal operating point of the DG and CB combination to carry the maximum load during the islanded network operation under power supply‐demand imbalance conditions. For the second stage, an analytical approach is proposed to identify the best operating power factor for the DG‐CB combination, calculating the power loss, and under‐utilization of the installed real‐reactive power sources. Simulation results on the IEEE 33‐bus grid‐dependent distribution network demonstrate that the proposed IJaya significantly improved the network performance and outperforms various existing optimization methods. In addition, during the network's islanded operation, maintaining the network power factor equal to the source power factor ( pf source ) makes the DG‐CB combination operate at their rated capacities. Abstract : The results demonstrate that, compared to the existing techniques, the proposed IJaya produces 0.01%−37.58% more reduction in power losses and up to 3.1% more voltage improvement for the grid‐connected network. During the islanded operation, the adopted analyzed approach revealed that non‐utilization of installed DG‐CB capacity varies up to 26.02% for the source power factor (pfsource) ranges from 0.8−0.93. If the mounted DGs‐CBs operate at pfsource, they can satisfy the energy needs of a larger share of the islanded network's load.